2021
DOI: 10.3389/fcell.2020.619199
|View full text |Cite
|
Sign up to set email alerts
|

A Holistic Systems Approach to Characterize the Impact of Pre- and Post-natal Oxycodone Exposure on Neurodevelopment and Behavior

Abstract: Background: Increased risk of oxycodone (oxy) dependency during pregnancy has been associated with altered behaviors and cognitive deficits in exposed offspring. However, a significant knowledge gap remains regarding the effect of in utero and postnatal exposure on neurodevelopment and subsequent behavioral outcomes.Methods: Using a preclinical rodent model that mimics oxy exposure in utero (IUO) and postnatally (PNO), we employed an integrative holistic systems biology approach encompassing proton magnetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 55 publications
1
35
0
Order By: Relevance
“…Intriguingly, a mouse self-administration model of oxy showed that chronic oxy use altered the expression of several ephrin and semaphoring genes associated with axon guidance [32]. We have also previously shown alterations in axon guidance systems in our study of pre-and postnatal oxy exposure [7]. The differential regulation of these pathways may contribute to impaired neuronal structure and synaptic transmission in oxy-exposed individuals.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Intriguingly, a mouse self-administration model of oxy showed that chronic oxy use altered the expression of several ephrin and semaphoring genes associated with axon guidance [32]. We have also previously shown alterations in axon guidance systems in our study of pre-and postnatal oxy exposure [7]. The differential regulation of these pathways may contribute to impaired neuronal structure and synaptic transmission in oxy-exposed individuals.…”
Section: Discussionmentioning
confidence: 51%
“…The cell pellet was lysed in RIPA buffer containing 1× protease and phosphatase cocktail inhibitor, followed by incubation on ice for 15 min. The samples were then sonicated three times at five-second intervals, followed by centrifugation at 10,000 RPM for 15 min at 4 • C. Protein quantification was carried out using Pierce BCA protein assay (Thermo Scientific, Rockford, IL, USA) as described in our earlier studies [6,7,[42][43][44][45][46]. A total of 50 µg of protein per sample per group was taken, and detergent was removed by chloroform/methanol extraction.…”
Section: Quantitative Proteomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a pre- and post-natal oxy exposure rat model previously established in our lab, we employed a mass spectrometry-based proteomic approach to examine changes in the SV proteome from postnatal day 14 (P14) offspring from the in utero and post-natal oxy exposed offspring [ 11 , 17 , 18 ]. Subsequent pathway analysis of SV signatures highlighted several functional pathways affected by the differential expression of these SV signatures.…”
Section: Introductionmentioning
confidence: 99%
“…Protein quantification was performed using Pierce BCA protein assay (Thermo Scientific, Rockford, IL, USA), as described in our earlier studies [51][52][53][54][55]. The mass spectrometry analysis was performed by a UNMC Mass Spectrometry Core (Omaha, NE, USA), and the protocol was based on the label-free quantitative mass spectrometry protocol described in our recently published studies [55][56][57].…”
Section: Mass Spectrometry Analysismentioning
confidence: 99%